Dielectric enhancement of Ba0.7Sr0.3TiO3/Ba0.5Sr0.5TiO3 multilayered thin films fabricated by chemical solution deposition. (1st January 2012) - Chang, Qing; Dai, Jianming; Zhu, Xuebin; Wu, Dajun; Zhang, Weijie; Sun, Yuping
Multilayered Ba0.7 Sr0.3 TiO3 /Ba0.5 Sr0.5 TiO3 thin films with different deposition sequences were deposited on Pt/Ti/SiO2 /Si substrates by chemical solution deposition method. Obvious dielectric enhancement occurred in Ba0.7 Sr0.3 TiO3 /Ba0.5 Sr0.5 TiO3 multilayered thin films due to Maxwell-Wagner affect, but not happened in Ba0.5 Sr0.5 TiO3 /Ba0.7 Sr0.3 TiO3 multilayered thin films because of the different interface quality caused by different deposition sequences. The dielectric constant and tunability of Ba0.7 Sr0.3 TiO3 /Ba0.5 Sr0.5 TiO3 multilayered thin films at 200 kHz (590 and 46%, respectively) were higher than that of Ba0.7 Sr0.3 TiO3 and Ba0.5 Sr0.5 TiO3 monolayer thin films (470, 32% and 430, 29%, respectively). Besides, the dielectric loss tangent of Ba0.7 Sr0.3 TiO3 /Ba0.5 Sr0.5 TiO3 multilayered thin films (0.025) was lower than that of Ba0.7 Sr0.3 TiO3 and Ba0.5 Sr0.5 TiO3 monolayer thin films (0.033, 0.052, respectively). Comparing with that of Ba0.7 Sr0.3 TiO3 and Ba0.5 Sr0.5 TiO3 monolayer thin films, the dielectric properties of Ba0.7 Sr0.3 TiO3 /Ba0.5 Sr0.5 TiO3 multilayered thin films had certain of improvement, which is of benefit to applications in tunable microwave devices.